(3GdLGUQ daQGFV ebOeI GHf HGHTGP aj GdfMhs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s ((3eMeO Hf GdeQJVi Hf eaUd Hf efUhQ s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CfRd GdbQBf eaUMkG HaVd Yde GdEYQGH s
(3BNQgG (B:s
(3agPG eG CQOfG PcQg ef ahGFO gPg GdebOeI aef CWdY Ydi Pdc adjUdMg , hdjTQcfG ai OYGFg s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3fMh (B121) s
Keywords: (3GdfMhs